2019
DOI: 10.1016/j.amsu.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral primitive neuroectodermal tumor associated with paraneoplastic Cushing's syndrome: The rare case

Abstract: IntroductionPrimitive neuroectodermal tumors (PNET) form a group of tumors defined by their appearance that are thought to develop from primitive (undifferentiated) nerve cells in the brain. They are rare tumors and their incidence is not well defined.Case presentationAn 18-month-old male presenting with typical Cushingoid appearance (moon face, central obesity, hirsutism and growth arrest) was admitted for evaluation of endocrine problems. Subsequent laboratory studies revealed markedly elevated adrenocortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In this case, the patient presented with features of CS and was evaluated accordingly. There has been only one previous case report of an 18-month-old patient with similar features which was found to be PNET on evaluation 9. In our patient on confirmation of CS, the high ACTH pointed towards Cushing disease (CD) or ectopic ACTH secretion.…”
Section: Discussionmentioning
confidence: 44%
“…In this case, the patient presented with features of CS and was evaluated accordingly. There has been only one previous case report of an 18-month-old patient with similar features which was found to be PNET on evaluation 9. In our patient on confirmation of CS, the high ACTH pointed towards Cushing disease (CD) or ectopic ACTH secretion.…”
Section: Discussionmentioning
confidence: 44%
“…40 Rahbar et al presented a case of Cushing's syndrome due to adrenocorticotropic-secreting peripheral PNET. 41 de Souza Azevedo et al reported of synchronous orofacial granulomatosis associated with MEC, however, the identification of associated pathological processes as a PNS is difficult depending on the constancy shown in a series of cases. Such large casuistic is difficult to obtain in rare tumors.…”
Section: Discussionmentioning
confidence: 99%
“…PNETs belong to the Ewing sarcoma family of tumours (ESFTs), which was first described in 1921 by James Ewing from the case of a 14-year-old female with a malignant bone tumour composed of small round cells [ 9 ] . PNETs are considered to be highly malignant tumours composed of small round cells originating from neuroectodermal tissue that attack the central nervous system or peripheral organs, varying in clinical presentation based on the origin of the tumour [ 10 ] . Usually, radiological and pathological work-ups are associated with misdiagnosis [ 11 ] .…”
Section: Discussionmentioning
confidence: 99%